rácticas de enseñanza de lógica matemática en educación inicial en la Escuela Diana Spencer. - Coral Vaca, Jacqueline Fernanda (2016)
For years, in Ecuador teaching of mathematics in schools it has not shown significant progress. Research has shown that this is consistent with what happens in initial teacher training for teaching mathematics. This study was carried out in the Diana Spencer School with children / as initial II and seeks to describe the experience of teaching practice, where specific resources, methodology, evaluation is used, among others, in the process of mutual learning in logical-mathematical area, the same that has been raised with the support of the Unit for Special Qualification of the Salesian Polytechnic University; we proceeded to witness first teaching practice in the area of logical mathematical Initial Level, considering the components of the curricular structure of a class, such as: planning, organization of work of learning, implementation of teaching and learning, teacher-student interaction, strategies learning experience, evaluation activities and forms of academic tasks. Consequently, presents main findings and conclusions of this case study, structured from the systematization, analysis and description of the information collected by direct observation sheet classes, field diary and record of interview the teacher, is a job that It is back with a theoretical framework that deals with the practice of teaching mathematical logic and the elements of a lesson plan.